Influences of Typhoon Chanchu on the 2006 South China Sea summer monsoon onset - Jiangyu Mao; Guoxiong Wu (Geophysical Research Letters)
This study reveals some unique features associated with the impact of Typhoon Chanchu on the South China Sea (SCS) summer monsoon (SCSSM) onset in 2006. With Typhoon Chanchu entering the SCS in mid‐May, southwesterlies were induced over the SCS and its upstream region due to a thermally forced Rossby wave response, leading to a reversal of low‐level winds and a positive meridional temperature gradient (MTG) in the upper troposphere over the SCS. Typhoon Chanchu thus acted as an immediate trigger for the SCSSM onset, and the onset date was suggested to occur in the third pentad of May. After the typhoon landed in the coast of southern China, it still contributed to the establishment of the SCSSM due to warming the air column over the northern SCS, resulting in a persistent positive MTG with the ridge surface tilting northward.